Design framework to renewal abandoned areas in historic districts - Ren Zhou; Zi Yang; Jia Liu; Jialing Chen; Weimin Guo (Journal of Asian Architecture and Building Engineering, 2025)
Urbanization and population growth have profoundly impacted the environment of historic and cultural blocks, resulting in a lack of public buildings and spaces for internal adjustment, fostering pronounced homogeneity. This study focuses on completely abandoned areas within historical streets, integrating space syntax analysis with semantic analysis to explore reshaping regional public buildings. Unlike previous studies centered around restoring old objects, the abandoned disconnected areas require a novel regional public architecture design framework through the semantic transformation of archival photographs, historical plans, and local culture. Taking Huishan Ancient Town in Wuxi as a case study, this research comprehends the abandoned disconnection area through a literature review and examination of archival data. By using spatial syntax analysis to combine the overall pedestrian flow space with the depth of ancient historical plans, entrances are set according to the pedestrian flow, preserving unique spatial characteristics and transforming the abandoned land into new public building spaces with distinct regional and contiguous features. Through semantic translation rooted in local culture, classical elements were extracted from intangible cultural heritage and applied to the ancient town’s architectural facades, navigation systems, and structures, thereby mitigating homogenization tendencies in both spatial and cultural elements.